Samuel Pinheiro Guimarães e o Plano Brasil 2022 - Amorim, Wilson Silva (2016)
This research aims to examine: the relationships between the struggling forces in the power bloc during the Lula government, when there was a relative improvement of the insertion of the grand bourgeoisie; and Samuel Pinheiro Guimarães Neto theoretical and political positions expressed in its two main books (Quinhentos anos de periferia and Desafios brasileiros na era de gigantes) and in the elaboration of the Brazil Plan 2022